Determinants of Clinical Diphtheria After Sub National Diphtheria Immunization Days In 2012 At Bangkalan - Utama, Feranita; Wahjuni, Chatarina Umbul; Martini, Santi (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTThe government had held sub-national diphtheria immunization days in 2012 to combat an outbreak of diphtheria in East Java province. However, there werestill regencies or cities which had high incidence and Bangkalanregencywas the highest. The research aimed to analyze the determinants of diphtheria in Bangkalan after SNIDs. This research was case control study with 31 subjects as case and 124 as control spread in 25 case villages and 25 control villages. Bivariate analysis used chi-square and simple logistic regression. Multivariate analysis used logistic regression. Bivariate analysisresult showed that individual and household variables that had associate with incidence of diphtheria in the Bangkalan after SNIDs of diphtheria vaccine in 2012 were DPT immunization status, the status of SNIDs, age, and mothers education level. In this study, there were not associate between village variables with diphtheria in the Bangkalan after SNIDs. Multivariate analysis result showed that had associate with incidence of diphtheria in Bangkalan after SNIDs were no DPT immunization (p=0,012; OR=4,765), incomplete DPT immunization (p=0,001; OR=6,276), 3-7 years of age (p=0,014; OR=15,137), 7-15 years of age (p=0,001;OR=41,984), and no immunization in SNIDs (p=0,020; OR=3,553). Conclusion, the dominantfactors that affected diphtheriainBangkalanwere status of DPTimmunization, ageand the SNIDs of diphtheria. Recommendation, DPTimmunizationshould becomplete, boosterimmunization should be needed, monitoring theimplementation ofsubPIN should be strict, especially inschool, and thecoverage ofDPT3andsubPIN should be increased and its report should be improved.Keywords: diphtheria, sub-nationaldiphtheriaimmunization days, DPT                              immunization